Cultural anthropology - Kottak, Conrad Phillip (Boston : McGraw-Hill, 2002)
What is anthropology? In the field. Culture. Language and communication. Ethnicity. Race. Making a living. Kinship and descent. Political systems. Marriage. Gender. Religion. The arts. The modern world system. Colonialism and development. Cultural exchange and survival. Applied anthropology.
Includes bibliographical references (p. 469-510) and indexes.
Keywords: Ethnology; Ethnology